2023
DOI: 10.3847/1538-4357/acaa9b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Star Formation Efficiency in the Central Regions of Nearby Quasar Hosts

Abstract: We combine Atacama Large Millimeter/submillimeter Array and Multi Unit Spectroscopic Explorer observations tracing the molecular gas, millimeter continuum, and ionized gas emission in six low-redshift (z ≲ 0.06) Palomar–Green (PG) quasar host galaxies to investigate their ongoing star formation at roughly kiloparsec-scale resolution. The AGN contribution to the cold dust emission and the optical emission-line flux is carefully removed to derive spatial distributions of the star formation rate (SFR), which, com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 210 publications
1
8
0
Order By: Relevance
“…The star formation activity distribution was confirmed with newly developed integrated field unit (IFU) observations (Perna et al 2021;Lamperti et al 2022;Molina et al 2022). The significant star formation activity has also been confirmed by a combination of optical and submillimeter observations (Molina et al 2023). Previous IRAM and ALMA observations have already suggested that I Zw 1 has a rich molecular gas reservoir, mainly concentrated in its circumnuclear zone Eckart et al 1994;Schinnerer et al 1998;Tan et al 2019).…”
Section: ( )mentioning
confidence: 58%
See 4 more Smart Citations
“…The star formation activity distribution was confirmed with newly developed integrated field unit (IFU) observations (Perna et al 2021;Lamperti et al 2022;Molina et al 2022). The significant star formation activity has also been confirmed by a combination of optical and submillimeter observations (Molina et al 2023). Previous IRAM and ALMA observations have already suggested that I Zw 1 has a rich molecular gas reservoir, mainly concentrated in its circumnuclear zone Eckart et al 1994;Schinnerer et al 1998;Tan et al 2019).…”
Section: ( )mentioning
confidence: 58%
“…Assuming a MW-like α CO increases the molecular gas surface density significantly, while the data points are still close to a ULIRG-like KS relation, and are still well above the KS relation for local star-forming galaxies (Figure 7). Nuclear starbursts have also been found in other low-z quasars (Cresci et al 2004;Schweitzer et al 2006;Romeo & Fathi 2016;Molina et al 2023).…”
Section: Star Formation Law Of the Nuclear Regionmentioning
confidence: 84%
See 3 more Smart Citations